2013
DOI: 10.3892/or.2013.2373
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the GnT-V gene inhibits metastasis and invasion of BGC823 gastric cancer cells

Abstract: Abstract. Metastatic and invasive potential is a barrier to the successful treatment of gastric cancer. N-acetylglucosaminyltransferase V (GnT-V), a key enzyme catalyzing the formation of 1,6 N-acetylglucosamine (GlcNAc), has been demonstrated to display a distinct function in different types of tumors. The aim of this study was to investigate the role of GnT-V in the invasive potential of BGC823 human gastric cancer cells in vitro and the possible underlying mechanism. GnT-V was downregulated in BGC823 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
(45 reference statements)
2
14
0
Order By: Relevance
“…For example, a close association was identified between GnT-V activity and tumor invasiveness in the sera of patients with HCC (19). Additionally, in vitro GnT-V-knockdown may decrease the invasive ability of the BGC823 gastric cancer cell line (11). Notably, the present results demonstrated that suppressing the expression of GnT-V markedly reduced cell-to-cell adherence and the invasive abilities of the SMMC-7721/R cells.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…For example, a close association was identified between GnT-V activity and tumor invasiveness in the sera of patients with HCC (19). Additionally, in vitro GnT-V-knockdown may decrease the invasive ability of the BGC823 gastric cancer cell line (11). Notably, the present results demonstrated that suppressing the expression of GnT-V markedly reduced cell-to-cell adherence and the invasive abilities of the SMMC-7721/R cells.…”
Section: Discussionsupporting
confidence: 56%
“…N-glycosyltransferase-V (GnT-V), as a key member of the glycosyltransferase family, is closely associated with the proliferation, migration and invasion of cancer cells (6)(7). Previous studies reported that GnT-V is commonly overexpressed in various advanced tumor types, including prostate cancer, oral squamous cell carcinoma, colorectal and breast cancer, gastric cancer cells and ovarian mucinous cancer (8)(9)(10)(11)(12)(13). Notably, previous studies identified that the downregulation of GnT-V markedly suppressed the proliferation and migration of tumor cells, and induced cell apoptosis (11,14,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This structure was catalyzed by UDP-N-acetylglucosamine: α-6-D-manno-side β1–6-N-acetylglucosaminyltransferase (EC2.4.1.155) which was known as GnT-V. Expression levels of β1,6-GlcNAc branched N-glycan and GnT-V were associated with metastasis in human digestive cancers such as colorectal carcinoma and gastric cancer (Seelentag et al, 1998; Kim et al, 2008; Huang et al, 2013; Huang, B. et al, 2014). In our previous studies, we have found this glycoform was increased in epithelial mesenchymal transition (EMT) process of Huh7 HCC cell and it might be a metastasis-promoting glycoform in HCC (Li, S. et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Epithelial–mesenchymal transition is related to cancer invasion and metastasis [27,28]. TGF-β1 may induce EMT by down-regulating E-cadherin and up-regulating vimentin in GC cells [29].…”
Section: Resultsmentioning
confidence: 99%